Rethinking Assessment in the Digital Age: Pedagogical Implications and Challenges - Nadya Fadillah Fidhyallah; Rizka Zakiah; Kusworo (The Indonesian Institute of Science and Technology Research, 2025)
The digital revolution has transformed various aspects of education, including assessment practices. This article explores the pedagogical implications and challenges of rethinking assessment in the digital age. Grounded in current literature, the article presents a conceptual framework for digital assessment and discusses the key aspects of assessment innovation, technological integration, and equity concerns. Drawing from recent empirical and theoretical contributions, this study argues that assessment must evolve to reflect the demands of 21st-century learning. The results and discussion are organized into three sections: innovative assessment models, technology integration in assessment, and equity and accessibility. Each section includes an analysis supported by a data table. The study concludes with a call for reflective and inclusive assessment design responsive to digital learning environments.